ASCETICISM AND SELF-PURIFICATION IN THE FOLKLORE OF PRABU SILIWANGI: A SYMBOLIC STUDY AT THE CITARUM SITE - Thariqq Syah, M Kautsar; Nurcahya, Yan; Sugiarto, Deri; Qolbiya Sakinah, Syahidah; Aufaa Ahdillah, Zaahidah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
This study aims to examine the fundamental differences between folklore and history, as well as how both contribute to the understanding of collective identity and cultural heritage in Indonesia. This research is significant given the relatively recent development of folklore as an independent academic discipline in Indonesia and the need to conceptually distinguish it from scientific historiography. The study employs a descriptive qualitative approach, utilizing literature review and field observations at cultural heritage sites such as Patilasan Dipatiukur and Prabu Siliwangi. The data analysis applies an interpretive method to explore narratives and cultural symbols embedded in both folklore and historical artifacts. The findings reveal that although folklore does not rely on empirical evidence like history, it holds essential value as a collective reflection of community experiences, imagination, and aspirations. In contrast, history requires verifiable sources as its foundation. These findings underscore the importance of preserving both as integral parts of the nation’s collective memory. The study implies the need for a synergistic approach that combines folkloristic and historiographical perspectives in education and cultural preservation. The originality of this research lies in its integrated approach, combining narrative analysis with the exploration of historical sites to trace the interconnection between collective memory, myth, and historical fact within the context of contemporary Indonesia.